PENGARUH PERILAKU KEWARGANEGARAAN ORGANISASI (PKO) TERHADAP KEPUASAN KERJA PADA PERAWAT DI RSUP PERSAHABATAN - Indah Novianti; Suparno Eko Widodo (Journal of Research and Measurement in Psychology, 2013)
Abstract The study was conducted to determine the effect of Organizational Citizenship Behaviour (OCB) to Job Satisfaction the sampel of the study nurses were at the Persahabatan hospital. Using 125 nurses working in RSUP Persahabatan as sample. This study used quantitative method. Incidental sampling was used as sampling technique. The meansure of Job satisfaction variables in this study using instruments Job Satisfaction Scale (JSS) and OCB variables in this study was method using instrumen OCB by Organ. Regression analysis performed with SPSS version 17.00 for windows. The study explains that there is significant influence between Organizational Citizenship Behaviour (OCB) to Job Satisfaction. Regression equation obtained is Y = 75,410 + 0.381 witch means there is a positive influence between job satisfaction with the OCB with the value F = 6.960; p = 0.009 (Î± <0.05). The determinant index (R Square) to the occurrence of job satisfaction and OCB shows 5.4% and the remaining 94.6% is influenced by other factors beyond job satisfaction. Keyword: Job satisfaction, Organizational Citizenship Behavior